Artificial Intelligence as an Instructional Tool for Developing paragraphs writing skill in EFL Classroom - Naila Lutfia; Ilham (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study aims to explore how the use of AI interacts with paragraph writing pedagogy, its impact on paragraph writing skills, and the problems students face in integrating technology into the learning process. Data were collected using a quantitative approach, a single-group quasi-experimental pre-test and post-test design, in which a single experimental group was evaluated without involving a control group, and targeted information about the diversity of AI writing tools and their impact on the writing quality of EFL students at Muhammadiyah University Mataram. The main applications used were ChatGPT and Grammarly. All participants agreed that the use of AI tools contributed positively to paragraph writing quality, particularly by enhancing content development and organizational coherence. It should be clarified that the findings of this study suggest that the integration of AI tools can be beneficial in improving the writing quality of EFL students. The results show that, based on Table 7, it is clear that the paired sample test results table shows a Sig value of 0.000, which is less than 0.05. This means that H0 is rejected, and H1 is accepted. It is therefore stated that perceptions of AI have a significant impact on descriptive paragraph writing learning methods for students in EFL classrooms.